Intracranial Tumor Control Following Immune-Related Adverse Events and Discontinuation of Immunotherapy for Melanoma. (16th November 2020) - Zhang, Michael; Rodrigues, Adrian; Bhambhvani, Hriday; Fatemi, Parastou; Pollom, Erqi; Gibbs, Iris; Thomas, Reena; Hancock, Steven; Soltys, Scott G; Chang, Steven D; Reddy, Sunil; Hayden, Melanie; et al.
Abstract: INTRODUCTION: Immunotherapy for melanoma patients with brain metastasis has significantly improved outcomes; however, they have also been characterized by potentially dangerous immune-related adverse events (IRAEs). Several reports suggest these reactions can precede improved treatment responses. METHODS: We conducted a retrospective chart review of melanoma patients who underwent immunotherapy treatment following diagnosis of brain metastasis. The study cohort was then stratified into two groups based on their history of developing an IRAE that prompted discontinuation of that regimen. The primary outcome variable included intracranial progression-free survival (PFS). Kaplan-Meier and Cox proportional hazard analysis were used to evaluate survival and predictors of outcomes. RESULTS: Fifty-two patients met inclusion criteria, seventeen of whom experienced severe IRAEs that led to discontinuation of immunotherapy. Median intracranial PFS was 19.9 vs 10.5 months ( P  = .053) in patients who did and did not experience severe IRAEs prompting discontinuation, respectively. No additional outcome benefits were identified for systemic PFS or overall survival, mean (21 months and 26.2 months, respectively). Multivariable analysis identified BRAF mutation status as a negative prognosticator of brain progression ( P  = .013, HR = 3.90). Initial treatment with BRAF inhibitor was also a negative predictor of all-cause mortality ( P  = .015, HR = 10.73). CONCLUSION: Immune related adverse events may signify an underlying immunogenic response that has intracranial disease control benefits. Despite their associated side effects, immunotherapies continue to demonstrate promising outcomes as a first-line agent for melanoma with brain metastasis.